Experimental analysis of crack initiation and growth in welded joint of steel for elevated temperature - Burzić, Meri (Materiali in tehnologije, 2008)
This paper presents results of experimental investigation of crack resistance by static and variable loading of alloyed steel A-387 Gr. 11 for elevated temperature application and its welded joint. Using SEN-B, CT and Charpy pre-cracked specimens, the significance of heterogeneity of microstructure and mechanical properties of welded joints on fracture toughness and fatigue crack initiation and propagation, at room and working temperatures, is evaluated.
Keywords: legirana jekla; zvari; lomna žilavost; razpoke